Is the Isthmus Location an Additional Risk Factor for Indeterminate Thyroid Nodules? Case Report and Review of the Literature - Pontieri, Gilda; Urselli, Francesca; Peschi, Livia; Liccardi, Alessia; Ruggiero, Anna Rita; Vergara, Emilia; Bellevicine, Claudio; Troncone, Giancarlo; De Palma, Maurizio; Biondi, Bernadette (Frontiers in Endocrinology, 2018)
ABSTRACT BACKGROUND: The management of indeterminate thyroid lesions is controversial. The American Thyroid Association guidelines suggest a conservative approach for low risk indeterminate thyroid lesions (TIR3A). CASE REPORT: We report a clinical case of a young girl who had TIR3A in a thyroid nodule located in the isthmus. After considering clinical and ultrasound risk factors, we assessed literature data and guidelines to plan the extension of surgery. We found several studies supporting that the isthmus malignant lesions were associated with a higher rate of multifocality, capsular invasion, extrathyroidal extension and central lymph node metastases. These data could predict a more aggressive behavior and a poor prognosis of the isthmus thyroid cancer compared to differentiated thyroid cancer, originating in the thyroid lobes. On the basis of these literature data and considering the familial risk for thyroid cancer of our patient, we decided to perform a total thyroidectomy. The histological examination revealed a follicular variant of papillary carcinoma located in the isthmus with capsular invasion. CONCLUSION: The isthmus location could be an additional risk factor to consider for a correct surgical approach in indeterminate thyroid lesions and thyroid cancer at fine-needle aspiration. We suggest that a careful ultrasonography should be carried out in patients with isthmus nodules. Total thyroidectomy should be performed in aggressive nodular disease. Prospective studies are needed to establish the best treatment for these lesions.